Shazam! ; Shazam!. Fury of the gods : 2-film collection [videorecording (Blu-Ray + DVD)] - Lemke, Darren; Strong, Mark, 1963-; Herman, Faithe, 2007-; Gayden, Henry; Morgan, Chris (Screenwriter); Levi, Zachary, 1980-; Angel, Asher, 2002-; Grazer, Jack Dylan, 2003-; Zegler, Rachel, 2001-; Brody, Adam, 1979-; Butler, Ross, 1990-; Cotrona, D. J. (Donald Joseph), 1980-; et al. (Warner Bros. Entertainment Inc., 2023)
Shazam! Fury of the gods. "Billy Batson--aka Shazam!--and his fellow foster kids are still learning how to juggle teenage life with having adult Super Hero alter egos, but a vengeful trio of ancient gods has arrived on Earth in search of the magic stolen from them long ago. Now, Billy and his family are thrust into a battle for their superpowers, their lives and the fate of their world"--Container.